Spring feeding by pink‐footed geese reduces carbon stocks and sink strength in tundra ecosystems - RENÉ Van Der WAL; SOFIE SJÖGERSTEN; SARAH J. WOODIN; ELISABETH J. COOPER; INGIBJÖRG S. JÓNSDÓTTIR; DRIES KUIJPER; TONY A. D. FOX; A. D. HUISKES (Global Change Biology, 2007)
Tundra ecosystems are widely recognized as precious areas and globally important carbon (C) sinks, yet our understanding of potential threats to these habitats and their large soil C store is limited. Land‐use changes and conservation measures in temperate regions have led to a dramatic expansion of arctic‐breeding geese, making them important herbivores of high‐latitude systems. In field experiments conducted in high‐Arctic Spitsbergen, Svalbard, we demonstrate that a brief period of early season belowground foraging by pink‐footed geese is sufficient to strongly reduce C sink strength and soil C stocks of arctic tundra. Mechanisms are suggested whereby vegetation disruption due to repeated use of grubbed areas opens the soil organic layer to erosion and will thus lead to progressive C loss. Our study shows, for the first time, that increases in goose abundance through land‐use change and conservation measures in temperate climes can dramatically affect the C balance of arctic tundra.